Descriptive Meta-Analysis: Implications of Business Combinations on Financial Performance and Corporate Strategy - Safitri, Tsamara; Panjaitan, Gloria; Athaya, Nada; Tamba, Rani; Gautama, Bana (Indonesian Journal Publisher, 2025)
This study is a descriptive meta-analysis that aims to identify and evaluate the impact of business combinations on financial performance and corporate strategy. By analyzing 52 scholarly journals from 2014 to 2025, this study maps empirical findings from various research contexts and methods. The results of the analysis show that 30 studies found significant effects of business combinations on financial performance, such as improvements in ROA, ROE, and NPM, while 14 studies showed strategic impacts such as market expansion, product diversification, and competitive advantage. However, there were also 8 studies that found no significant effect on either variable. This research emphasizes the importance of synergy, integration readiness, and vision alignment of vision in ensuring the success of business combinations. The findings are expected to serve as a reference for managers, investors, academics, and regulators in formulating appropriate policies and strategies in planning mergers and acquisitions.